62.3k views
0 votes
A student is trying to solve the system of two equations given below: Equation P: a + b = 6 Equation Q: 4a + 2b = 19 Which of the following steps can be used to eliminate the a term? −1(4a + 2b = 19) −4(4a + 2b = 19) −4(a + b = 6) 4(a + b = 6)

User Tjs
by
4.5k points

1 Answer

0 votes

Answer:


-4(a + b = 6)

Explanation:

Given


a + b = 6


4a + 2b = 19

Required

Eliminate a

Multiply the first equation by -4


-4(a + b = 6)

Add to the second equation


-4(a + b = 6) + (4a + 2b = 19)

Solve brackets


(-4a -4b = -24) + (4a + 2b = 19)

Open bracket


-4a + 4a -4b + 2b = -24 + 19


-4b + 2b = -24 + 19

At this point, a has been eliminated;

From the list of given options, the option that answers the question is
-4(a + b = 6)

User Edixon
by
4.9k points